Persuasive strategies in the discourse of popular psychology and linguistic techniques of its realization (on the example of the texts from women’s sites); SGEM. 2nd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, Vol. 2 - Kurikova N. V. Nataljya Vladimirovna (Education and Educational research, 2015)
Title screen